Technical Efficiency and Financial Feasibility of Drift Net Fishing Business in Tanjung Pasir Village, Indragiri Hilir, Riau - Chicka Willy Yanti; Rindi Metalisa; Nida Wafiqah Nabila M Solin (Berkala Perikanan Terubuk, 2023)
Efficiency is an important aspect that can be used as a benchmark for making decisions in production with various available production input alternatives. Knowing efficiency both technically and economically will reduce the gap between productivity that should be produced. Efficiency is used as an indicator in seeing the ability of the production unit in the fishing business, to know the potential for production inputs it is necessary to analyze its efficiency both technically and economically as well as its development potential. So this research was conducted to see how the efficiency of the dominant fishing gear used by fishermen in Tanah Merah District is technically by looking at the factors that affect fishing production and its financial feasibility. This study uses a quantitative descriptive analysis with a survey method approach and uses an analysis of technical efficiency and financial feasibility. The results showed that the technical efficiency of the capture fisheries business using drift nets by looking at the Cobb-Douglas production function showed a VRS value of 1.185 > 1, which means that it is in the increasing return to scale category where the percentage increase in production is greater for the addition of production factors so that the use of production factors is technically efficient. . Based on the results of the financial feasibility analysis it was concluded that the fishing business using drift nets is feasible to be cultivated in terms of financial parameters in the form of R/C ratio, PPC and ROI.